Exploring the Si Slamet program: whats impact of the technology-based emergency service system in solving Batang Regency's health problems? - Haniifah, Matsna (BKM Public Health and Community Medicine, 2021)
Objective: This paper explores emergency cases' handling by the district government of Batang through a technology-based health service system. Content: The Batang Regency government optimises easy-to-reach and responsive public services for medical emergency services through Sistem Informasi Spesial Keselamatan Elektronik Terpadu (Si Slamet). This system is supported by artificial intelligence technology that is integrated with health facilities and across sectors. The principles promoted are anti-discrimination, responsiveness, fast and precise handling. The services provided are free for payment and are held 24 hours in 7 days. One of the services is offering directions firsthand by telephone and accelerating emergency events by sending victims' images to streamline response time. This system has four post location points located in the Center, Tulis District, Subah District, and Gringsing District because these four points are located on the main route (Pantura), prone to traffic accidents. This innovation program has succeeded in assisting in preventing disability and reducing the mortality rate due to emergencies. In 2019 there were 295 emergency cases and 525 non-emergency cases that Si Slamet successfully served. Existing cases such as trauma from KLL, maternity, internists, work accidents, fires and others. However, some people do not know about this innovative program. The existence of an optimal level of awareness in the community is one of the reasons. Also, health workers' ability to gain patient trust is a challenge in obtaining patient satisfaction by building empathy. In implementing this program, the health office coordinates with cross-sectors such as PMI, the police, and health service facilities. Therefore, the health office needs to disseminate information to the community to increase awareness and intensify training for human resources involved in the program to improve the quality of services.